(untitled) (Minerva, 2019)
The genre of the ’polyanthea’ (a gathering of quotations by different authors grouped under their subject matter) enjoyed considerable success as an auxiliary tool for ’professional writers’ in the sixteenth and seventeenth centuries. One of the most conspicuous examples was D. Nani Mirabelli’s Polyanthea (1503), augmented by B. Amantius and F. Tortius (1585) and augmented again and refashioned by J. Lang (1607). This paper compares the entry ’eloquentia’ in Mirabelli’s original version and in J. Lang’s deeply refashioned edition (1607): after the more than hundred years between both, rhetoric is no longer portrayed in mainly negative tones and the sources at disposal of the polyanthea user have not only considerably grown, but are also conceived of as belonging to clearly predefined categories (such as quotations from pagan and Christian authors, exempla, apophthegms, emblems, etc.). All it is but one more sample of the increasingly central role that rhetoric played in sixteenth-century cultural life and intellectual activity.